DISPARITAS GENDER DALAM PARTISIPASI SEKOLAH DI DAERAH PERDESAAN INDONESIA: SUATU PENDEKATAN UNITARI - LOSINA PURNASTUTI (Jurnal Penelitian Humaniora, 2003)
Abstract Using the 1993 Indonesia Family Life Survey, this paper examines the school participation among boys and girls in rural Indonesia and investigates why parents are less likely to keep their daughter in school. The analysis based on indicators of school attendance. In particular we focus on the effect of gender discrimination, the differential effect of parents’ education and employment, household resource constraints, location of the household and quality of the school. This paper found significant gender differences in children’s education. Parents are more likely to send their sons to school rather than their daughters. However, parents’ education has significant positive impact on their children’s schooling in different manner. Mothers’ education has stronger impact on girls’ education, while fathers’ education, has stronger impact on boys’ education. Household income matters for girls; it implies that education is a luxury good for girls. Further the household size has significant negative impact on the children’s schooling. Keywords: children’s schooling, gender differences, unitary model, collective model, bargaining model, Indonesia